Sporadic Case of dyschromatosis universalis hereditaria showing moderate response to narrow-band ultraviolet-B - Sarita Sasidharanpillai; Amal Shyam; Shiny P Manakkad; Ettapurath N Abdul Latheef; Saleem Rahima; Nina Paul (Wolters Kluwer Medknow Publications, 2019)
Dyschromatosis universalis hereditaria (DUH) is a rare genodermatosis where the affected manifests mottled pigmentation with intermingled hyper- and hypo-pigmented macules. On most occasions, the lesions begin on limbs and then extend to trunk. Most of the cases reported in literature are from Japan. It is rarer in Indians. In this report, we describe a 12-year-old male child with DUH, who showed response to narrow-band ultraviolet-B therapy.